Prevention of Registration of Interfaith Marriages Through Sema Number 2 of 2023 - Fahmi, Irfan; Windiantina, Wiwin W. (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2024)
Interfaith marriage in Indonesia is still controversial even though Law No. 1/1974 on Marriage explicitly states that marriage must be carried out by the laws of each religion and belief. In practice, cases of interfaith marriage still often occur in the community. Meanwhile, human rights and pluralism activists argue that everyone has the right to form a family, including through interfaith marriage, so the state should not prohibit it. This controversy was reignited when several District Courts granted applications to register interfaith marriages in 2022-2023. In response, the Supreme Court (MA) issued Supreme Court Circular Letter (SEMA) Number 2 of 2023 which essentially prohibits courts throughout Indonesia from granting registration of interfaith marriages. This policy has been appreciated by conservative religious circles, but regretted by human rights activists. They believe that the SEMA has the potential to violate the freedom of religion and family guaranteed by the Constitution. This study aims to analyze SEMA No.2/2023 in managing requests for registration of interfaith marriages The study aims to offer insights into the Supreme Court's policy and the challenges encountered by courts, providing constructive suggestions for future interfaith marriage policies.